Clinical Outcomes of Oral Antibiotic Switch in Children with Staphylococcus aureus Bacteremia - Salih Demirhan; Brenda I. Anosike (Turkish Archives of Pediatrics)
Objective: Staphylococcus aureus is one of the leading causes of bacteremia in children. In this study, we aimed to evaluate our center’s experience on the etiology, management, and outcomes of pediatric Staphylococcus aureus bacteremia (SAB) with particular focus on transitioning to oral antibiotic therapy.